Mitos Satu Suro dan Sistem Kepercayaan Lokal dalam Tradisi Jaranan di Desa Majenang, Kabupaten Lamongan: Kajian Etnografi - Like Zanjabil Anfa'ullinaas; Abdul Halim (Institut Seni Indonesia Padangpanjang, 2025)
Majenang Village in Lamongan Regency, East Java, maintains various cultural traditions that continue to be practiced by the local community, particularly during the commemoration of the night of Satu Suro. This night is regarded as a sacred moment associated with spiritual reflection, ancestral respect, and communal rituals. One of the prominent traditions performed on this occasion is the jaranan performance, a form of traditional folk art that contains elements of spirituality and local belief. This study aims to examine the myth of Satu Suro and its relationship with the local belief system reflected in the jaranan tradition in Majenang Village. Using an ethnographic approach, data were collected through observation, interviews with community members, and documentation of ritual activities. The findings show that the jaranan performance during the Satu Suro commemoration functions not only as a cultural performance but also as a medium for expressing collective beliefs, maintaining social solidarity, and reinforcing the cultural identity of the community. The myth of Satu Suro plays an important role in shaping the community's perception of sacred time and guiding ritual practices that connect social life with spiritual values. This tradition continues to be preserved as part of the cultural heritage and belief system of the Majenang community